Occupational allergy after exposure to caddis flies at a hydroelectric power plant. Issue 6 (June 1994) - Kraut, A; Sloan, J; Silviu-Dan, F; Peng, Z; Gagnon, D; Warrington, R
Abstract : A cross sectional survey was conducted in a hydroelectric power plant in which the workforce was exposed to large numbers of caddis flies. 28 of 57 employees participated. About 50% of the participants reported work related eye, nose, and sinus symptoms and wheezing. Working in locations with greater exposure to caddis flies was significantly associated with work related symptoms. 17 workers (61%) were skin prick positive to a laboratory prepared caddis fly antigen (LCFA) made from the remains of caddis flies present in the plant and 11 (39%) had positive reactions to a commercial caddis fly antigen (CCFA). Workers stationed in heavily exposed areas were 3.7 times as likely to have a positive response to the LCFA (p = 0.009) and 5.3 times as likely to have a positive response to the CCFA (p = 0.036). 13 (46%) of survey respondents reported three or more work related symptoms. 10 (91%) CCFA positive workers reported three or more work related symptoms. Pulmonary function studies revealed slight, but not significantly decreased forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and FEV1/FVC ratios in workers who were skin test positive to either caddis fly preparation when compared with those who were negative. One worker who was skin test positive to both antigens had a cross shift fall in FEV1 of 20% predicted. Occupational allergy to caddis flies proved to be a significant health problem at this work site.